Answer: A. 14
Step-by-step explanation:
If e=9 and c=5 you would replace e+c with those
9+5=14
Please insert your equation number
Answer:
Step-by-step explanation:
9 + 4 = 13 Two minus' make a plus
14-9 = 5 this is just subtraction
-4 + 5 = 1 two minus's make a plus.
-7-9 = -16
Answer:
C
Step-by-step explanation:
The multiples of 3 are
3, 6, 9, 12, 15, ...........
The terms form an arithmetic sequence with common difference of 3.
The sum to n terms is
=
[2a₁ + (n - 1)d ]
where a₁ is the first term and d the common difference
Here a₁ = 3 and d = 3, thus
=
[ (2 × 3) + (139 × 3) ]
= 70(6 + 417) ] = 70 × 423 = 29610 → C